Formation of the Projection of Global Interests on Latin America - Маковський, С. О.; Макеєнко, Л.Ф. (Київський національний університет імені Тараса Шевченка, 2025)
The article examines the historical relations between Latin America and foreign countries, focusing on the "conquest", colonial and post-colonial periods, analyzes the long-term influence of colonialism on the development of Latin America. It highlights how external forces shaped the region's political and economic systems, leaving a legacy of social stratification and economic dependence. The first part of the article is devoted to the analysis of the complex and ambiguous process of conquest and its impact on the formation of Latin America as a region, demonstrating the fundamentality, duality and legacy of the aforementioned process. The second part of the article analyzes in detail the economic-political system and social structure of colonial Latin America, formed under the influence of the metropolises, and demonstrates what consequences it had for the future independent states. The third part of the article analyzes the process of gaining independence by the countries of Latin America, emphasizing that although internal contradictions in colonial societies were an important factor, it was the weakening of the metropolises and the external intervention of other states that played a decisive role in the successful conclusion of the wars of independence. And at the very end, an analysis of the economic dependence of Latin American countries on external players in the period after gaining independence, which was a consequence of its colonial legacy. Describes the emergence of new interested players in the arena: Great Britain and the United States, emphasizes that the debt problem led to defaults and deepening economic addiction. In general, the article argues that the historical experience of foreign intervention in the internal affairs of Latin America has had a lasting impact on the development of the region. The legacy of colonialism, the debt cycle, and foreign interventions continue to shape the political, economic, and social realities of Latin American countries.

Стаття досліджує історичні взаємини між Латинською Америкою та іноземними державами, зосереджуючись на “конкістському”, колоніальному та пост-колоніальному  періодах, аналізує тривалий вплив колоніалізму на розвиток Латинської Америки. Вона підкреслює, як зовнішні сили формували політичні та економічні системи регіону, залишаючи спадщину соціальної стратифікації та економічної залежності. Перша частина статті присвячена аналізу складного та неоднозначного процесу конкісти та її впливу на формування Латинської Америки як регіону, демонструючи  фундаментальність, двоїстість та спадщину вищезгаданого процесу. Друга частина статті детально аналізує економіко-політичну систему та соціальну структуру колоніальної Латинської Америки, сформовану під впливом метрополій та демонструє, які наслідки це мало для майбутніх незалежних держав. Третя частина статті аналізує процес здобуття незалежності країнами Латинської Америки, підкреслюючи, що хоча внутрішні суперечності в колоніальних суспільствах були важливим чинником, саме ослаблення метрополій та зовнішнє втручання інших держав відіграли вирішальну роль в успішному завершенні воєн за незалежність. І на сам кінець аналіз економічної залежності латиноамериканських країн від зовнішніх гравців у період після здобуття незалежності, що стало наслідком її колоніальної спадщини. Описує появу на арені нових зацікавлених гравців: Великої Британії та США, підкреслює, що проблема заборгованості призводила до дефолтів та поглиблення економічної аддикції. Загалом, стаття стверджує, що історичний досвід зовнішнього втручання у внутрішні справи Латинської Америки мав тривалий вплив на розвиток регіону. Спадщина колоніалізму, цикл боргів та іноземні інтервенції продовжують формувати політичні, економічні та соціальні реалії латиноамериканських країн.
Становлення проекції глобальних інтересів на Латинську Америку
Keywords: Latin America; LATIN AMERICA AND CARIBBEAN; conquest; economic exploitation; demographic changes; colonial economy; economic dependence; economic reform; social hierarchy; government crisis; wars of independence; foreign intervention; political instability; foreign capital; economic instability; debt crisis; Латинська Америка; ЛАКБ; конкіста; економічнаексплуатація; демографічнізміни; колоніальнаекономіка; економічназалежність; економічна реформа; соціальнаієрархія; урядова криза; війни за незалежність; зовнішняінтервенція; політичнанестабільність; іноземнийкапітал; економічнанестабільність; боргова криза